O ENEM como via de acesso do surdo ao ensino superior brasileiro - Briega, Diléia Aparecida Martins (2017)
The study performed in this dissertation is focused on the access to Brazilian Higher Education by deaf people through Enem [Brazilian High School National Examination]. It analyzes accessibility as a principle, such as mentioned by Davidov (1987), who provides full mediation of knowledge and the successive and conscious character of school education. Such accessibility concept exceeds the provisions of Brazilian legislation and rise debates on Enem’s offer to deaf people who are fluent in Brazilian Sign Language (Libras – BSL). Enem construct was created based on strictly set criteria and procedures, and test developers are not aware on the linguistic singularity of deaf people. Brazilian Sign Language has been considered only in the operation of SL interpreters (SLI), who require in the exam a greater attention on its practice. Society is “deaf” before SLI, with different processes of Sign Language appropriation and rare appropriation of written Brazilian Portuguese as a second language. In this view, Enem, as a construct developed to check psychological agencies and measure the concepts learned by High School graduate students, is taken by deaf people in limiting conditions. For obtaining this research data, one used the mixed method to analyze documentary sources and extracted microdata including quantitative data of who took Enem in 2010 and 2011. The information sources were documents publicly available on the website of Instituto Nacional de Estudos e Pesquisas Educacionais [Brazilian Institute of Studies and Educational Researches] (INEP), such as Enem pedagogical reports, technical summary from Higher Education Census, and handbooks for training developers about the items of the exam. Choosing the two-year period 2010-2011 derived from the difficulty to access the data regarding the target-public of specialized services in Enem, which is included in 2009-2010 reports but in a similar manner, considering the rearrangement of the reference matrixes only for 2010 and 2011. By using statistical analysis software, one found data on the resources request and assistances in Sign Language and on the mark achieved by deaf people in the four fields of Enem. It was made a descriptive analysis of the requests, which pointed out to the registration increase of deaf people along with the improvement of the available resources, with possibility of requesting extra time, SLI, accessible classroom, among other options that overcome architectural and communication barriers. As the statistical analysis proposed by IRT [Item Response Theory], one should review the difficulty level of the items of the exam, as this level is measured without considering the needs of those who have Brazilian Portuguese as a second language. It is required to further analyze the main subject, considering the issues highlighted and the concerns related to SLI’s work in tests and exams, mainly regarding the understanding of Brazilian Portuguese texts or the translation of questions, as there is a gap in the current legislation enabling the creation of a Banco Nacional de Itens (BNI) [National Bank of Items] in Sign Language. Therefore, this work meets the investigation concerns about deaf people’s education field, from the view of the constructs used by Brazilian and foreign government bodies little explored in previous researches. Due to represent this innovation, it brings implications through researches that may be developed in the future. It is also worth highlighting that the low index of admissions to undergraduate courses by means of Enem requires a long-term follow-up for building a changing analysis of this educational rise process experienced by the deaf person.